(untitled) (The Review of Diabetic Studies, 2024)
Background: Botulism is a rare disease, and infant botulism (IB) even rarer, especially when steering the condition to honey consumption. IB is considered a life-threatening disease as it leads to severe neurological symptoms. Exploring the knowledge, attitude, and practice (KAP) among mothers on the relationship between honey and IB will help public health professionals implement appropriate maternal health education materials targeting infant health and increase the awareness of the paediatric primary care providers, physicians, and nurse practitioners about the risk of IB among their patients. Objectives: To determine the knowledge of mothers from Makhah city in Saudi Arabia (SA) regarding IB and assess their attitude and practice towards feeding honey to their infants before 12 months of age. Methods: Using a comparative cross-sectional study, in February 2022, we broadcasted an online questionnaire through social networking and evaluated the KAP of 385 mothers. Results: Less than half (48%) of the mothers have heard about IB, 40% of them knew the relation between honey ingestion and IB and only 6.5% acknowledged that they knew the causative agent for IB. The prevalence of feeding honey to infants before 12 months was 52%. Mothers from Makkah city were less likely to provide honey to their infants (p=0.002). Conclusion: The study revealed that mothers from makkah city have relatively low knowledge of IB and that they hold favourable perceptions of using honey as a food supplement and feeding honey to their infants before 12 months. Considering the high prevalence of honey feeding with the known low incidence of IB in SA, Medical professionals should consider IB in their differential diagnosis particularly in the presence of neurological symptoms.